Analisis Harga dan Kualitas Produk terhadap Minat Beli Konsumen pada Toko Emas Sinar Baru Sampit - Ayu , Novi; Andryati, Yuli (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study explains whether there is an effect of price on purchase intention and product quality on purchase intention. The data collection technique used was a questionnaire with 100 respondents. While the data analysis technique used is quantitative analysis, using multiple linear regression. The sampling technique used was purposive sampling. The results of the study are price has a positive and significant effect on buying interest in Sampit Baru Sinar Baru shop, product quality has a positive and significant effect on buying intention of Sampit Baru Sinar Emas shop.